Dinamika Konsep Gharar dalam Transaksi Keuangan Perspektif Ulama Fikih Klasik - Affero, Muhammad Izzam; Mustofa, Imron (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: The concept of gharar in classical Islamic law is one of the fundamental principles in Islamic financial and economic transactions. Gharar refers to uncertainty or excessive risk in an agreement that can cause injustice to one of the parties. This study aims to analyze the dynamics of the concept of gharar from the perspective of classical scholars, such as Imam Al-Ghazali, Ibn Qudamah, and Ibn Taimiyah, as well as its application in contemporary economic transactions. The research method used is a qualitative approach with a literature study on classical and modern literature. The results of the study show that gharar is categorized into two, namely gharar fahish (excessive), which is forbidden, and gharar yasir (light), which is tolerated in Islamic law. This concept plays an important role in ensuring fairness and legal certainty in Islamic financial transactions. This study contributes to understanding the principles of muamalah fiqh and the urgency of stricter regulation in the Islamic finance industry to avoid gharar practices in modern transactions, such as conventional insurance and uncertainty-based investment schemes. Keywords: Gharar, classical Islamic law, uncertainty, financial transactions, Islamic finance. Abstrak: Konsep gharar dalam hukum Islam klasik merupakan salah satu prinsip fundamental dalam transaksi keuangan dan ekonomi Islam. Gharar merujuk pada ketidakpastian atau risiko berlebihan dalam suatu akad yang dapat menimbulkan ketidakadilan bagi salah satu pihak. Penelitian ini bertujuan untuk menganalisis dinamika konsep gharar dalam perspektif ulama klasik, seperti Imam Al-Ghazali, Ibn Qudamah, dan Ibn Taimiyah, serta penerapannya dalam transaksi ekonomi kontemporer. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi pustaka terhadap literatur klasik dan modern. Hasil kajian menunjukkan bahwa gharar dikategorikan menjadi dua, yaitu gharar fahish (berlebihan) yang diharamkan dan gharar yasir (ringan) yang ditoleransi dalam hukum Islam. Konsep ini berperan penting dalam memastikan keadilan dan kepastian hukum dalam transaksi keuangan syariah. Studi ini memberikan kontribusi dalam memahami prinsip-prinsip fiqh muamalah dan urgensi regulasi yang lebih ketat dalam industri keuangan Islam untuk menghindari praktik gharar dalam transaksi modern, seperti asuransi konvensional dan skema investasi berbasis ketidakpastian. Kata Kunci: Gharar, hukum Islam klasik, ketidakpastian, transaksi keuangan, keuangan syariah.